Mastering sculpture : the figure in clay : a guide to capturing the human form for ceramic artists - Córdova, Cristina, 1976- (Quarry Books, 2022)
"Mastering Sculpture: The Figure in Clay is a comprehensive workshop on sculpting the human form from head to toe for ceramic artists"--